Fascia-derived stem cells enhance fat graft retention by promoting vascularization through the HMOX1-HIF-1α pathway - Guo Chen; Jie Long; Yuge Zhang; Xuhua Zhou; Botao Gao; Zijin Qin; Yuhan Zhu; Binyu Song; Ziwei Cui; Zhangzi liu; Man Xu; Zhou Yu; et al. (Stem Cell Research & Therapy)
Abstract Background Adipose tissue is a widely used autologous soft tissue filler in plastic surgery, particularly for volumetric restoration in cases of soft tissue deficiency. However, effectively controlling the retention rate of transplanted fat remains a major challenge. Therefore, this study aims to explore strategies to enhance fat graft retention. We isolated fascia-derived stem cells (FDSCs) from human superficial fascia and compared their gene expression profiles with those of adipose-derived stem cells (ADSCs). Through bioinformatics analysis and functional experiments, we identified significant differences in the angiogenic potential of the two cell types. Based on sequencing results, we further investigated the roles of hypoxia-inducible factor-1α (HIF-1α) and heme oxygenase-1 (HMOX1). This study highlights the critical potential of FDSCs in improving fat graft retention and promoting angiogenesis, offering new strategies for enhancing graft survival and optimizing tissue regeneration therapies. Methods We isolated fascia-derived stem cells (FDSCs) from human superficial fascia and compared them with adipose-derived stem cells (ADSCs). RNA sequencing was performed to analyze gene expression profiles, followed by bioinformatics analysis to identify differences in angiogenic potential. Functional experiments were conducted to investigate the roles of HIF-1α and HMOX1 in angiogenesis. Results RNA sequencing revealed significant gene expression differences related to angiogenesis in FDSCs. The expression levels of HMOX1, HIF-1α, and VEGFa were significantly higher in FDSCs than in ADSCs, and HMOX1 positively regulated the expression of HIF-1α and VEGFa. In vitro experiments demonstrated that FDSCs promoted angiogenesis more effectively than ADSCs. In vivo co-transplantation experiments further confirmed that FDSCs improved fat graft retention and vascularization. Conclusions We demonstrated that FDSCs can more effectively promote vascularization both in vitro and in vivo, and significantly improve graft retention, indicating their broad potential for future applications in tissue repair and regeneration.